Nilai Religius pada Cerpen Ciumlah Aku di Ujung Subuh Karya Hamzah Puadi Ilyas - Deasy Wahyu Hidayati (Imajeri: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
The purpose of this study is to find a description of the elements or religious values ​​contained in the short stories of Kiss Aku di Ujung Subuh by Hamzah Puadi Ilyas. The method in this study is a descriptive qualitative research method. The religious value in the short story Kiss Aku di Ujung Subuh by Hamzah Puadi Ilyas shows that there is religious value in the aspect of belief in Allah, including believing in angels, the Day of Judgment, the prophet's ark, and believing in the Koran and hadiths; religious value in the aspect of awe of the majesty of God includes amazement at the aroma of wickedness, the power of God, and the creation of the universe; religious values ​​in the aspect of the vibration of a personal conscience include a heart vibration of gratitude, cries of events, past memories, and dreams; religious values ​​in the aspect of personal attitudes include the attitude of worship, prostrate, makeistigfar, dhikr, and read the Koran / juz-amma; and religious values ​​in the aspect of mental intimidation include intimidation of the soul from karma, the core process of death, and the process of taking one's life. Based on the results of this study, it can also be seen that the religious value that appears most in the short stories of Ciinum Aku di Ujung Subuh by Hamzah Puadi Ilyas is personal attitude. Keywords: Score; Religious; Short story; High school